An Extension of Theory of Planned Behavior: Role of M- Commerce Adoption in Rajasthan - Jain, Prashasti; Bhati, Narender Singh (International Journal of Psychosocial Rehabilitation, 2020)
With higher advancement in the area of technology and internet, mobile internet device has created an opportunities for electronic-businesses to take the advantage of mobility. Therefore, currently, mobile commerce (m-commerce) has proved to have huge impact on business growth and its’ survival. M-commerce, is a method of buying products and services anywhere, using a wireless device having internet accessibility. In current era, mobile phone is not just a device to make calls and text messages, but also used to perform financial transactions and providing many more value added services. Therefore, the current study focuses on extending and examining the Theory of Planned Behavior (TPB) developed by Ajzen, 1991, with a view to study the user’s’ m- commerce service adoption in Rajasthan state. The study was conducted using a structured questionnaire from m- commerce services users in Rajasthan. All three determinants of purchase intention were studied i.e. Subjective Norms, Attitude, and Perceived Behavioral Control (PBC). Regression analysis was used to predict the effect of determinants TPB on users’ adoption of m-commerce. The findings reveled a significant and positive effect of subjective norms, attitude, and perceived behavioral control (PBC) on users’ intention towards adopting m- commerce services.